Artificial Intelligence Techniques Between the Difficulties of Using and Improving the Quality of Auditing: An Exploratory Study of a Sample of Academics and Professionals in the Kurdistan Region – Iraq (Raparin Journal of Humanities (RJH), 2025)
This study aims to shed light on the extent to which the use of artificial intelligence techniques contributes to improving the quality of auditing and to highlight the difficulties and obstacles artificial intelligence faces. To achieve the aims of the research, the descriptive analytical approach was used, and a questionnaire was designed and distributed to a random sample consisting of (external auditors, and academic individuals specialized in the field of accounting and auditing) in the Kurdistan Region – Iraq and are (57) in total, and this is to determine the extent to which the chosen sample is aware of the importance of using artificial intelligence in improving the auditing process. The study has reached a number of recommendations, the most important of which are: the use of artificial intelligence by external auditors helps in improving the auditing process by reducing time and the cost of the audit process and accuracy in extracting data and classifying them which in turn helps in enhancing the audit process. The study had several recommendations, the most important of which were: the need to deal with the difficulties and obstacles in the way of the auditing process in light of the use of artificial intelligence techniques in a rational manner, with the aim of keeping pace with modern developments in general and at a professional level in particular, and the need to enhance the awareness of auditors of the importance of using artificial intelligence techniques in the audit process with the aim of publishing knowledge related to these techniques and using them in an effective and an efficient manner to enhance the performance and quality of audit process.